2019
DOI: 10.1097/corr.0000000000000651
|View full text |Cite|
|
Sign up to set email alerts
|

Surgical Loupes Worn by Orthopaedic Surgeons Are a Reservoir for Microorganisms

Abstract: Background Surgeons frequently use optical loupes to magnify the surgical field; they are typically unprotected when positioned directly over the wound, where particulate shedding containing microorganisms could potentially lead to surgical site infections (SSIs). SSIs are rare in some orthopaedic subspecialties such as hand surgery; however, in other subspecialties, for example, the spine, where surgeons often use loupes, SSIs can have devastating consequences. Qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Weiner and colleagues [10] reported that use of surgical loupes or microscope in simulated spine surgery was associated with increased bacterial shedding compared to controls. The current study by Graham and colleagues [5] demonstrates that surgical loupes are contaminated with bacteria and/or fungi at very high rates, which can be decreased by cleaning with an alcohol swab. These findings are important because loupe contamination may be a potential source of surgical field contamination that can be easily addressed.…”
mentioning
confidence: 64%
“…Weiner and colleagues [10] reported that use of surgical loupes or microscope in simulated spine surgery was associated with increased bacterial shedding compared to controls. The current study by Graham and colleagues [5] demonstrates that surgical loupes are contaminated with bacteria and/or fungi at very high rates, which can be decreased by cleaning with an alcohol swab. These findings are important because loupe contamination may be a potential source of surgical field contamination that can be easily addressed.…”
mentioning
confidence: 64%
“…It was also evident there were proponents of loupes and those who were less enthusiastic (Table 3). Another potential negative factor is that recent study has demonstrated that loupes can act as a surface for microbes—however there is insufficient evidence to suggest that this could be linked to increased surgical site infections 21,22 . Nevertheless, routine cleaning of loupes should be recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Many regularly touched surfaces represent fomites ( Rusin et al., 2002 ; Gerba et al., 2016 ; Di Lodovico et al., 2018 ). Their microbial load is problematic especially in clinical environments ( Weber et al., 2010 ; Graham et al., 2019 ), where it contributes to hospital acquired infections and particularly threatens immunocompromised patients. This study focuses on slit lamps, optometric devices widely used in medical eye facilities, characterized by surfaces with close contact to the examiner and many different patients.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, special hygienic attention is required for optical surfaces. Previous studies revealed a significant and diverse bacterial load on optical devices, such as microscopes ( Fritz et al., 2020b ), surgeons loups or surgeons eyeglasses ( Graham et al., 2019 ; Butt et al, 2021 ) and reusable tonometer tips ( Hillier and Kumar, 2008 ). They all contained significant amounts of bacteria, including many species known to cause skin and eye infections and with a potential to carry antibiotic resistances.…”
Section: Introductionmentioning
confidence: 99%